Effect of CMC on the stability of ZnO nanofluid at high temperature and salinity - Adil, M. (American Institute of Physics Inc., 2016)
In this research, the critical micellar concentration (CMC) of different anionic surfactants was determined by employing the UV-Vis spectroscopic technique. The CMC is crucial to evaluate the adsorption of anionic surfactant on a surface of charged metal oxide (i.e. zinc oxide), to prepare a stable nanofluid for different applications including enahced oil recovery (EOR). Three anionic surfactants (sodium dodecyl sulfate, sodium dodecylbenzenesulfonate and oleic acid) were studied in this research. The amount of CMC was determined in the deionized water and brine solution, using the values from the data extracted from the graph between absorbance and concentration of surfactants. A comparative study was also conducted based on CMC results that shows a good agreement between the present research and the literature. In addition, the effect of temperature on CMC value was also examined which provide a better stability of ZnO nanofluid in the high-temperature environment. The overall result reveals that with an addition of salt to the anionic surfactant, repulsive force increases which lead to a decrease in the CMC value. Whereas with the increase in temperature the free energy of the system is affected the result in an additional decline in CMC. However, this decrease is higher in a case of SDS and relatively lower in the case of SDBS and oleic acid. These results suggest that CMC play a significant role to tailor a stable dispersion, to match the conditions of the corresponding application. Â© 2016 Author(s).